Plastic Waste and Its Impact on Environmental Life and Sustainable Development: An Applied Study on Al-Ardah Governorate - KSA - ALabdali, Abdullah Ahmad (Journal of natural sciences, life and applied sciences, 2022)
The study aimed to identify plastic waste and its impact on environmental life and sustainable development in Al-Ardah Governorate (Kingdom of Saudi Arabia). To filfil the objectives, this research is based on the use of descriptive and analytical statistical methods which seeks to describe the phenomenon in reality and diagnose it in order to treat it and find the relationships between the variables associated with this phenomenon. This approach is based on the use of descriptive and analytical statistical methods through the use of various data collection tools, namely, questionnaire, interview, observation and others.The results showed that one of the most important effects of plastic waste on environmental life is that it causes environmental pollution that causes the death of millions of marine creatures annually, and plastic waste causes soil pollution, by forming an insulating layer between the soil, plants and their roots. It is also a threat to the ecosystem and health system, carcinogenicity of foods, and air pollution. Recycling plastic waste contributes to preserving the environment to a very high degree and helps create job opportunities by attracting companies and opening branches for them. It also helps to clean the environment, in addition to sustainable development. One of the most important ways to get rid of plastic waste in Al-Ardah Governorate is to make flyers through visual communication means, and to hold lectures and seminars in schools and universities about the danger of plastic waste to human life, the environment and sustainable development, followed by the importance of raising awareness of the dangers of plastic waste on the environment, imposing fines for littering plastic, providing a greater number of clean and environmentally friendly containers with printing posters that encourage the dumping of waste in their designated places, while providing marine supervision to ensure that plastic waste is not thrown in beaches. Plastic waste causes health risks to, humans, animals and plants, the proliferation of germs and microbes, and the infertility of breeding. The results showed that there are statistically significant differences between the views of community members in Al-Ardah Governorate about the impact of plastic waste on human and environmental life and the benefits of recycling plastic waste due to the difference in gender, the difference in the age group, the difference in the educational qualifications of the sample members, and the different years of experience of community members in Al-Ardah Governorate.
Keywords: plastic; waste; carcinogenic diseases; seas